Harnessing the Carniolan honey bee breed in maximizing productivity - Zelenina Olga; Pimkina Tatyana (BIO Web of Conferences)
Climate warming has been observed everywhere in recent years, including the Kaluga region. This makes it possible to use more heat-loving, intensively developing bee breeds for the production of beekeeping products. The aim of the research is to evaluate the possibility of using Carniolan bees in apiaries for the production of commercial honey. The material of the research were 4-frame honeycomb packages of bees purchased in the Republic of Uzbekistan. Bee families were placed in 12-frame hives designed for a standard nest frame of 300 mm high and 435 mm wide. Bee family development was monitored weekly by counting the number of frames fully occupied by insects. Honey production was estimated by weighing the honey produced by each family. During the development, the bee families were divided into three groups according to the age of the mothers or their turnover. At the beginning of the main honey collection, the average number of bee families in the three groups was 11.8±1.41 frames, and at the end of the season it was 9.8±1.86 frames. From I group of bee families, which did not show tendency to swarming, 25.1±8.63 kg of honey was obtained; from II group of bee families, which replaced mothers by spontaneous change, without swarming – 15.7±7.13 kg, from III group, into which bee families were divided, taking into account productivity of formed broods - 4,4±6,16 kg. Honey collection per each family of bees at the beginning of the period averaged 15.4±12.44 kg. The increase in the number of bee families during the season, taking into account the formation of brood and culling, amounted to 10%. The results of the research allow to recommend the use of the Carniolan breed of bees in the apiaries of Kaluga region.